Field site soil aquifer treatment shows enhanced wastewater quality: evidence from vadose zone hydro-geophysical observations - Sahya, A.; Sonkamble, S.; Jampani, Mahesh; Rao, A.N.; Amerasinghe, Priyanie (Elsevier, 2023)
Soil aquifer treatment (SAT) is an emerging, nature-based, economically viable wastewater treatment solution. Currently, most SAT experiments are done at the laboratory scale, which cannot generate the same conditions as natural field sites and limits the understanding of treatment efficiency. The current study carried out in situ SAT experiments in the Musi River basin in India, where wastewater irrigation is a common practice. SAT efficiency was determined using an integrated approach, including electrical resistivity tomography (ERT) surveys, soil investigations (grain size, permeability, and moisture measurements), and biochemical characterization of raw and SAT treated wastewater. The ERT scans of SAT column show lower order electrical resistivity 10-30 O-m with enhanced chargeability >5–6 mV/V attributed to the vadose zone, characterized by clay-rich soil and sandy soil up to 5–6 m depth. The increase in sand percentage (>70%) below 140–160 cm depth corroborates with the high moisture content (23.5%). The vadose zone permeability (K) 1.58 m/day and discharge (Q) 38.19 m3/day is used to determine the pollutants reduction efficiency of SAT column. Hydrogeological and biogeochemical observations reveal that the improved dissolved oxygen from <1.0 to 5–6 mg/L in the vadose zone catalyzes the oxidation of organic matter resulting in the reduction of BOD and COD up to 92% and 97%, respectively, and denitrification reducing NO3-- (0.55 kg/day). In addition, the precipitation and adsorption by kaolinite clay prompted the reduction of PO42- (0.26 kg/day). Furthermore, the oxic-vadose zone could not support the growth of coliforms and faecal coliforms, and the reduction observed was up to 99.99% in the SAT production well. Overall, the results indicated a positive outcome with SAT efficiency and framed the SAT sitting criteria for different geological environments.